Role of Character Education in Improving Self-Confidence of Early Childhood (Case Study at Aisyiyah Kateguhan Kindergarten, Sawit, Boyolali) - Faizah, Fera Nur; Zulkarnaen, Z (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study explores how character education initiatives at Aisyiyah Kateguhan Sawit Kindergarten contribute to the development of student self‑confidence. By situating character formation within a nurturing early‑childhood environment, the research seeks to demonstrate the role such programs play in preparing young learners for future academic and personal challenges. Methodology: Employing a qualitative design, data were gathered through direct classroom observations of character‑building activities and semi‑structured interviews with both teachers and students. Indicators assessed included the fidelity of character‑education implementation, the specific values emphasized (e.g., honesty, cooperation), and observable shifts in children’s confidence during routine tasks and special projects. Results: Quantitative summaries of the qualitative data show that 75% of students actively engaged in character‑education activities, and 70% could articulate and apply the targeted values in their interactions. Classroom observations revealed that 80% of children displayed noticeable self‑confidence in tasks such as storytelling and group presentations, with 75% showing marked improvement over the course of the program. Interview feedback indicated that 85% of students reacted positively to the character‑education curriculum, although 40% encountered occasional challenges—such as shyness during peer interactions or difficulty internalizing abstract values. In response, 60% of teachers introduced complementary strategies, including project‑based learning and structured group collaborations, to boost participation and reinforce key lessons. Applications/Originality/Value: By illuminating both the successes and obstacles of implementing character education at the kindergarten level, this study offers actionable insights for early‑childhood educators. Its findings underscore the importance of adaptive teaching methods—like collaborative projects and incremental value reinforcement—to foster self‑confidence effectively. These lessons can guide curriculum planners and school administrators in crafting holistic programs that not only advance academic readiness but also support children’s personal growth and community well‑being.